The Tectonics of the Double Skin:: Green Building or Just more Hi-Tech Hi-Jinx? NORTH AMERICAN CASE STUDIES: - Meyer Boake, Terri; Harrison, Kate; Chatham, Andrew (ARCC Conference Repository, 2019)
North American Double Façade Buildings: 1980 to 2001 Where over the past ten years, Europe and the Pacific Rim have seen the construction of a number of vanguard double skin façade buildings, very few have been either proposed or constructed in North America. The first to be constructed was the Occidental Chemical Center (also known as the Hooker Building) in Niagara Falls, New York. It was designed by Cannon Design Inc. and completed in 1980. Occidental Chemical has achieved historic status in texts on building systems as the first of its kind to be constructed in North America. In spite of much press and notoriety, its skin system was not widely adopted in commercial building types to follow. SOM designed a double skin envelope for the Prudential Life Insurance Company in Princeton, N.J. in the late 1980's.3 Following few built examples in the 1980's, it would appear that the double skin façade system continued without influence in North America during the 1990's. The next building of note is the double skin façade for the Seattle Justice Center designed by Arup Associates in 2000/ 2001.4 The European offices of Arup Associates have been responsible for many of the double façade buildings constructed to date in Europe and Asia. A double skin, referred to in this case as "une façade intelligente”, is being used on the "Caisse de Depots et de Placements du Quebec” in Montreal. Façade erection commenced during Winter 2002. They chose to use the system for its thermal, visual and acoustical properties. The double skin used, is a Twin-Face type and integrates an operable window. In designing for the severity of the Quebec climate they used double glazing on the outside and single glazing on the inside skin. Standard recommendations for Twin-Face systems would provide single glazing on the outside buffering skin and double glazing on the interior layer. This approach might work in more temperate climates, but is not suitable to a cold climate installation. Ongoing construction information on the CDP may be found at http://www2.destinationcdp.com/index.asp?version=3 The Telus Building in Vancouver, British Columbia, designed by Busby and Associates has been recently completed. This building varies from most other examples in that it uses the second skin to encapsulate an existing concrete masonry building, to prevent its destruction, extend its life and create an improved interior work environment.